ChemInform Abstract: Palladium‐Catalyzed Direct C2‐ and Further C7‐Acylation of Indoles with Aldehydes. Issue 39 (September 2015) - Zhang, Hui‐Jun; Wu, Zhengjian; Lin, Weidong; Wen, Ting‐Bin
Abstract The title reactions are accomplished by oxidative cross‐coupling of indoles [(I) and (VI)] with aldehydes (II) in the presence of tBu‐OOH as mild oxidizing agent catalyzed by Pd(OAc)2.